Factors predicting the adoption of e-government services in telecenters in rural areas: the mediating role of trust - Kamarudin, Syafila; Omar, Siti Zobidah; Zaremohzzabieh, Zeinab; Bolong, Jusang; Osman, Mohd Nizam (De la Salle University, 2021)
This study aims to inspect the factors that impact the adoption of e-government services (e-Gov) in telecenters in Malaysia and the mediating role of trust in this regard. A survey was conducted with the use of a questionnaire. The collected sample involved people who lived in rural areas and telecenters (N= 388). The results demonstrate that performance expectancy, social influence, and facilitating conditions are all directly and positively correlated with telecenter users’ intention to use e-Gov, which is directly related to the official usage of e-Gov in telecenters. The results showed that trust partially mediated between users’ intention and the actual usage of these services. This study has revealed that telecenters in Malaysia have opened up a unique window of opportunity for people who live in rural areas. This would help the Malaysian government and policymakers investigate the reasons for the current low penetration rate of e-Gov, and formulate methods to inspire the official use of e-Gov by those living in rural areas, where such facilities are still seen as an innovation.